PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP PERILAKU ETIS PEGAWAI SEKRETARIAT DIREKTORAT JENDERAL BEA DAN CUKAI - Priskilla, Vanesha; Marsofiyati, Marsofiyati; Febriantina, Susan (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to examine the influence of Emotional Intelligence and Spiritual Intelligence on the Ethical Behavior of Secretariat Employees of the Directorate General of Customs and Excise. Data collection in this research used secondary data from the company and a questionnaire in the form of Google forms using random sampling techniques. The sample used in this research was 170 employees from a total population of 250 employees. This research uses SPSS by calculating multiple regression analysis and testing data hypotheses. The results of this research show that Emotional Intelligence and Spiritual Intelligence have a significant effect on Ethical Behavior